Analisis Mengenai Sanksi Administratif Bagi Warga Yang Tidak Menggunakan Masker Pada Saat Keluar Rumah Di Magetan Berdasarkan Peraturan Bupati Magetan Nomor 32 Tahun - Ary Setiawan Prasetyo; Mochammad Alfan Bachtiar; Rizaldi Mochammad Alfin (UIN Syarif Hidayatullah Jakarta, 2022)
Covid-19 threatens world life. Indonesia detected the virus in early 2020. The virus has a bad reputation in the U.S. Central and Level II Regions have policies to disrupt the Covid-19 transmission chain. Magetan City has released Regent's Regulation number 32 of 2020 on Guidelines for the new normal order in the 2019 coronavirus illness (Covid-19) pandemic. The Magetan Regency government is trying to reduce health protocol violations including not wearing masks and not physically separating. Sanctions range from written warnings to fines.